ECOLOGICALLY AND ECONOMICALLY SUSTAINABLE AGRICULTURAL TRANSPORTATION BASED ON ADVANCED INFORMATION TECHNOLOGIES - Fazekaš, Tibor; Bobera, Dušan; Ćirić, Zoran (Economics of Agriculture, 2017)
In the modern world there are lots of considerations about transportation in general, including analysis and decision making about the current situation and planning as well,that means preparation for future needs through defning policies, goals and investments to design transportation networks and facilities. The environmental consequences of general transportation and agriculture itself are of special interest as well. Transport activities are given and unavoidable in every society, for any country, but their intensive practice often produces negative effects on surroundings. The quoted problem emerges in a special manner when observing merged - as agricultural transportation: modeling ecological issues here is particularly complex due to great number of variables and random elements dependent on subjectivity in decision making, appearance of unexpected events and often incorrect data. In this paper authors discuss different aspects of agricultural transportation and point out the importance of application of methods and models that are capable of treating uncertainties and are appropriate to keep under control the abundance of ecological effects of transportation in agriculture, making efforts towards the development of sustainable food and raw materials production.